(untitled) (Context: Journal of Interdisciplinary Studies, 2022)
Shabbir Akhtar, The Verses and the Fury Be Careful with Muhammad! Salman Rushdie and the Battle for Free Speech (2nd Edition with a New Preface). BIJAK Publishing, 2020. pp. 187. ISBN: 978-623-94742-2-5.